2017
DOI: 10.1016/j.celrep.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ras-Driven Cancer Cell Survival and Invasion through Selective Inhibition of DOCK1

Abstract: Oncogenic Ras plays a key role in cancer initiation but also contributes to malignant phenotypes by stimulating nutrient uptake and promoting invasive migration. Because these latter cellular responses require Rac-mediated remodeling of the actin cytoskeleton, we hypothesized that molecules involved in Rac activation may be valuable targets for cancer therapy. We report that genetic inactivation of the Rac-specific guanine nucleotide exchange factor DOCK1 ablates both macropinocytosis-dependent nutrient uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 46 publications
4
48
0
Order By: Relevance
“…We and others previously demonstrated that Rac GTPases regulate myeloid leukemia cell survival and engraftment in vivo (46, 47). Importantly, DOCK proteins play a key role in Ras‐mediated activation of the Rac pathway, which promotes cancer cell survival (48). We asked whether MBD3‐mediated regulation of DOCK is of potential clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…We and others previously demonstrated that Rac GTPases regulate myeloid leukemia cell survival and engraftment in vivo (46, 47). Importantly, DOCK proteins play a key role in Ras‐mediated activation of the Rac pathway, which promotes cancer cell survival (48). We asked whether MBD3‐mediated regulation of DOCK is of potential clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Such evidence of an oncogenic and metastasis promoting role for DOCK family members has led to an interest in the development of DOCK inhibitors. TBOPP, a DOCK1 selective inhibitor, inhibited tumor growth and metastasis in mice with lung carcinoma tumors (Tajiri et al, 2017). This compound also targeted DOCK1 in melanoma cells with the oncogenic Rac1 P29S mutation (Tomino et al, 2018).…”
Section: Targeting Docksmentioning
confidence: 99%
“…DOCK5 is a highly specific GEF for Rac1 GTPase, which is the major function of this protein [3,33,34]. Although whether the interaction between Rac1 and mTOR depends on its GDP/GTP loading state is still controversial, Rac 1 is critical for mTOR signaling regulation in both mTORC1 and mTORC2 [16,[35][36][37].…”
mentioning
confidence: 99%